2016
DOI: 10.1155/2016/8249843
|View full text |Cite
|
Sign up to set email alerts
|

Is Universal Screening Necessary? Incidence of Tuberculosis among Tibetan Refugees Arriving in Calgary, Alberta

Abstract: Background. Canadian policy requires refugees with a history of tuberculosis (TB) or abnormal chest radiograph to be screened after arrival for TB. However, Tibetan refugees are indiscriminately screened, regardless of preimmigration assessment. We sought to determine the incidence of latent (LTBI) and active TB, as well as treatment-related outcomes and associations between preimmigration factors and TB infection among Tibetan refugees arriving in Calgary, Alberta. Design. Retrospective cohort study including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The 39 included publications contained data on 31 598 migrants positive for LTBI. Studies were done in 13 countries, across three WHO regions (European region, region of the Americas, and Western Pacific region): Australia (n=4 studies), [31][32][33][34] Canada (n=3), [35][36][37] Germany (n=1), 38 Israel (n=1), 39 Japan (n=1), 40 the Netherlands (n=2), 41,42 Norway (n=2), 43,44 South Korea (n=1), 45 Spain (n=3), [46][47][48] Sweden (n=1), 49 Switzerland (n=1), 50 UK (n=4), [51][52][53][54] and USA (n=15). [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] In total, 25 studies with outcome data on 8764 migrants were used to calculate the proportion of individuals initiating treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 39 included publications contained data on 31 598 migrants positive for LTBI. Studies were done in 13 countries, across three WHO regions (European region, region of the Americas, and Western Pacific region): Australia (n=4 studies), [31][32][33][34] Canada (n=3), [35][36][37] Germany (n=1), 38 Israel (n=1), 39 Japan (n=1), 40 the Netherlands (n=2), 41,42 Norway (n=2), 43,44 South Korea (n=1), 45 Spain (n=3), [46][47][48] Sweden (n=1), 49 Switzerland (n=1), 50 UK (n=4), [51][52][53][54] and USA (n=15). [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] In total, 25 studies with outcome data on 8764 migrants were used to calculate the proportion of individuals initiating treatment.…”
Section: Resultsmentioning
confidence: 99%
“…[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] In total, 25 studies with outcome data on 8764 migrants were used to calculate the proportion of individuals initiating treatment. [33][34][35][36][37][38][39][41][42][43]48,[50][51][52][53][54][55][56][58][59][60]65,66,68,69 3A). Demographic and patient factors associated with noninitiation of treatment reported in the studies were being of sub-Saharan African origin 55 and being a refugee from sub-Saharan Africa, northern Africa, or the Middle East.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age, reported by 33% of studies [4,10,31,35,39,51,52,57,62,68,77,78,83,84,88,93,94], ranged from 3.5 to 39 years, with the lowest prevalence in a study that included only children (mean age 3.5 years). Only 21% of studies reported the prevalence by gender.…”
Section: Ltbi Prevalence Study Characteristics and Populationmentioning
confidence: 94%